Diagnostic Accuracy of Computed Tomography for Intestinal Obstruction Keeping Laparotomy as Gold Standard - Hafiza Ammara Khan; Muhammad Akhtar (Medical Journal of South Punjab, 2024)
Objective: To assess the diagnostic accuracy of computer tomography for intestinal obstruction, keeping laparotomy findings as a gold standard. Methodology: A Cross-sectional Validation study was performed in the Department of Radiology, Combined Military Hospital, Bahawalpur, from June 20th, 2023, to March 19th, 2024. An abdominal CT scan was performed on 130 patients with abdominal pain who were unable to pass stool. Based on the findings of CT for intestinal obstruction, these patients underwent surgery. The gross and histopathological results of the specimen were obtained to confirm the diagnosis taken as a gold standard examination. Percentage and frequency were used to analyze qualitative variables such as sex, the origin of intestinal obstruction, intestinal obstruction diagnosis by CT and laparotomy, plus histopathological results. Using 2x2 tables, the following metrics were calculated: sensitivity, specificity, and positive and negative predictive value. The laparotomy findings plus histopathological results of the samples collected during surgery were used as a gold standard to calculate the diagnostic accuracy of CT in the diagnosis of intestinal obstruction. Results: Overall sensitivity, diagnostic accuracy, specificity, negative and positive predictive value, and diagnostic accuracy in this study for CT compared to Laparotomy were 94.29%, 92%, 93.84%, 79.31%, and 98.02%, respectively. Post-stratification data based on age and gender showed greater sensitivity, specificity, and diagnostic accuracy in males and younger age groups. Conclusion: CT scan was a highly sensitive and specific method for detecting intestinal obstruction when histopathology was used as the gold standard.